PENGARUH KNOWLEDGE OF HEALTHY FOOD DAN HEALTH AWARENESS TERHADAP BEHAVIORAL INTENTION PADA KONSUMEN JASA KATERING MAKANAN SEHAT DI ANA KITCHEN GARUT - Muhamad Iqbal, - (2021)
This study aims to examine and to research the effect of knowledge of healthy food and health awareness toward consumer's behavioral intention of healthy food catering services in Ana Kitchen Garut. The research method used is descriptive quantitative by using data from interviews, observations, literature studies, and questionnaires. The study population was consumers who had or were currently using healthy food catering services in Ana Kitchen Garut. Questionnaire/questionnaire data were obtained by distributing them to 162 respondents using probability sampling techniques. The data analysis tool used is SPSS version 22.0 for windows. The results of this study show that the knowledge of healthy food and health awareness of consumer's behavioral intentions of healthy food catering services in Ana Kitchen Garut are included in both categories. Based on the tested hypothesis it shows that knowledge of healthy food and health awareness influences behavioral intention. This research issued implications that healthy food catering service providers such as Ana Kitchen Garut can educate their consumers about the importance of eating healthy foods and can innovate on the healthy food menu that has been offered before, also able to adjust the marketing strategies that have been applied in order to improve good ratings from consumers and maximizing the company's relationship with consumers so that it is easier to identify their desires more precisely. Keywords: Knowledge of Healthy Food, Health Awareness, Healthy Food, Behavioral Intention.